2015
DOI: 10.1038/srep16350
|View full text |Cite
|
Sign up to set email alerts
|

Sample storage conditions significantly influence faecal microbiome profiles

Abstract: Sequencing-based studies of the human faecal microbiota are increasingly common. Appropriate storage of sample material is essential to avoid the introduction of post-collection bias in microbial community composition. Rapid freezing to −80 °C is commonly considered to be best-practice. However, this is not feasible in many studies, particularly those involving sample collection in participants’ homes. We determined the extent to which a range of stabilisation and storage strategies maintained the composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
404
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(434 citation statements)
references
References 41 publications
23
404
1
6
Order By: Relevance
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 82%
“…The impact of the type of fecal sample collection method on microbial data has been considered in a number of previous studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, the majority of these studies were conducted in North American or European populations near academic or clinical laboratories and typically included only a small number of methods.…”
mentioning
confidence: 99%
“…RNAlater has also been tested in a number of studies (10, 20-24, 26, 30, 32), but the results varied. The majority of studies concluded that RNAlater was an acceptable preservative for microbial analyses of fecal samples (10,22,23,26,30), although in some studies, researchers detected decreased alpha diversity (20,21,30), decreased DNA purity or yields (21,24), or lower stability at room temperature for longer periods (33) compared with immediately frozen fecal samples. Storage of fecal samples in 70% ethanol does not appear to be suitable for microbiome analyses (10), but 95% ethanol has been previously observed to adequately preserve fecal samples (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in a number of previous studies have assessed different collection methods for fecal samples and the impact of leaving a sample at room temperature on the fecal microbiome (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The FOBT card, or a similar Whatman FTA card (GE Healthcare Life Sciences, Pittsburgh, Pennsylvania), has been tested in a few studies (10,21,26,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation